2015
DOI: 10.1111/brv.12205
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinarity to reconstruct historical introductions: solving the status of cryptogenic crayfish

Abstract: Anciently introduced species can be confounded with native species because introduction pre-dates the first species inventories or because of the loss of the collective memory of the introductions. The term 'cryptogenic species' denotes species of unknown or unclear status (native versus non-native) in a given territory, and disciplinary approaches are often insufficient for solving their true status. Here, we follow an integrative, multidisciplinary approach to solve the status of a cryptogenic species, propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 103 publications
1
40
2
Order By: Relevance
“…It has been recently suggested (Clavero and Villero 2013;Clavero et al 2015) that this species was not present in the Iberian peninsula before the seventeenth century, a limit based on the absence of any reference to the species in the Relaciones topográficas survey ordered by Philip II (henceforth Relaciones) which was undertaken between 1556 and 1598 (Clavero and Villero 2013). The first written document known to the latter authors that mentions crayfish in Spain dates from 1775.…”
Section: Origin Of the Spanish White-clawed Crayfishmentioning
confidence: 99%
“…It has been recently suggested (Clavero and Villero 2013;Clavero et al 2015) that this species was not present in the Iberian peninsula before the seventeenth century, a limit based on the absence of any reference to the species in the Relaciones topográficas survey ordered by Philip II (henceforth Relaciones) which was undertaken between 1556 and 1598 (Clavero and Villero 2013). The first written document known to the latter authors that mentions crayfish in Spain dates from 1775.…”
Section: Origin Of the Spanish White-clawed Crayfishmentioning
confidence: 99%
“…The documents showed that Spain's King Philip II had asked a member of his court to arrange for crayfish to be brought from Italy, and that the animals were shipped in 1588 (ref. 6) .…”
Section: Cautious Approachmentioning
confidence: 99%
“…However, catch rates from a 1905 fisherman's book were higher 1 , suggesting that the author might have described only his best trips. Similarly, Clavero's team backed up its finding 6 from the Spanishcourt letters with evidence from fields such as archaeology, linguistics, genetics and ecology.…”
Section: Cautious Approachmentioning
confidence: 99%
“…First, we point out that the mono-disciplinary approach followed by Matallanas et al (2016) is 17 much weaker than the transdisciplinary approach used and advocated by Clavero et al (2016).…”
mentioning
confidence: 93%